An alternative to traditional health care model: case MUFACE (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
MUFACE health model enables freedom of choice. The medical model does not prejudge whether public health is better than private or vice versa, since mutual MUFACE offers both health services produced by public companies and private companies. Guaranteed coverage by private insurance companies are equivalent to those of public health (the Common Services Portfolio SNS) and even more features. This model is more efficient (public health produces the same health services between 40% and 60% more expensive than the private sector), it gives users greater freedom (freedom of choice of doctor, specialist or hospital) and increased accessibility (there are no waiting lists).
Keywords: merit goods; effectiveness; efficiency; inefficiency; productivity; health service